A Novel Linear Evaluation of Chromatographic Peak Features in Pharmacopoeias Using an Inverse Fourier Transform Algorithm - Shuping Chen; Weiyuan Zhu; Sai Huang; Baoling Zheng (Biophysica, 2025)
The system suitability testing of chromatography is an indispensable procedure in pharmaceutical analysis, and it must comply with rules in related pharmacopoeias. An inverse Fourier transform algorithm was developed to accurately evaluate chromatographic features versus a standard Gaussian peak shape. The regular chromatogram is considered a pseudo-frequency spectrum and can be converted to a nominal time signal via inverse Fourier transformation. The system suitability parameters of peak width, theoretical plate number, tailing factor, and noise testing were evaluated using linear regressions directly and compared with the compendial rules. This novel method is simple, accurate, robust, reliable, and efficient for the evaluation of chromatographic peak features.